2015
DOI: 10.4049/jimmunol.1401344
|View full text |Cite
|
Sign up to set email alerts
|

Tumoral Expression of IL-33 Inhibits Tumor Growth and Modifies the Tumor Microenvironment through CD8+ T and NK Cells

Abstract: Cancer immunotherapy has shown great promise as a new standard cancer therapeutic modality. However, the response rates are limited for current approach that depends on enhancing spontaneous antitumor immune responses. Therefore, increasing tumor immunogenicity by expressing appropriate cytokines should further improve the current immunotherapy. Interleukin-33 is a member of the IL-1 family of cytokines and is released by necrotic epithelial cells or activated innate immune cells and is thus considered a “dang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
222
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(241 citation statements)
references
References 44 publications
16
222
2
1
Order By: Relevance
“…The reason for the discrepancy between these results and ours is not known, but we suspect that the concentration of IL-33 present within tumors is a critical factor determining the tumor microenvironment. One study (13) reported (12,13,40,41), whereas lower doses of IL-33 seem to induce vigorous proliferation of ILC2s, as shown in the present study. Our results suggest that ILC2-governed responses may override the CD8 + immune response enhanced by IL-33 due to the dominance of a Th2 microenvironment.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The reason for the discrepancy between these results and ours is not known, but we suspect that the concentration of IL-33 present within tumors is a critical factor determining the tumor microenvironment. One study (13) reported (12,13,40,41), whereas lower doses of IL-33 seem to induce vigorous proliferation of ILC2s, as shown in the present study. Our results suggest that ILC2-governed responses may override the CD8 + immune response enhanced by IL-33 due to the dominance of a Th2 microenvironment.…”
Section: Discussionsupporting
confidence: 83%
“…Similar mechanisms, such as the IL-33-induced increase in IFN-g and perforin effector activities induced by NK cells and CD8 + T cells, act on eradicating IL-33-secreting tumors (13). The reason for the discrepancy between these results and ours is not known, but we suspect that the concentration of IL-33 present within tumors is a critical factor determining the tumor microenvironment.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…IL-33 has also been shown to synergize with IL-12 to promote CD8 + T cell effector function [108]. In line with the ability of IL-33 to promote a CD8 + T cell response and the fact that CD8 + T cells mediate a vital role in the defence against cancer, over-expression of IL-33 potently inhibited tumour growth and metastasis in both B16 melanoma and 4T1 breast cancer models with both CD8+ T cell and NK cell numbers seen to be increased [109]. knockdown tumours as compared to the control tumours [29].…”
Section: "Wounds That Do Not Heal" -Understanding the Role Of Il-33 Imentioning
confidence: 88%
“…21 As IL-33 may signal via ST2 on MDSCs to control their numbers, this cytokine could be modulating their suppressor activity as well. To corroborate this, we measured the relative expression of two characteristic MDSC genes involved in their modulatory function, iNOS and Arg1.…”
Section: Discussionmentioning
confidence: 99%